Physical and Mechanical Properties of Coarse Bamboo Fibers Extracted by Different Techniques (Journal of Fiber Bioengineering and Informatics, 2023)
Bamboo fiber extraction methods include mechanical, stem explosion, water retting, enzymatic, and chemical methods. Each extraction method has drawbacks in terms of fiber quality, cost, efficiency, and environmental impact. The combined technique of fiber extraction was developed by combining two or more extraction methods in order to minimize the disadvantages of separate methods. This study developed and tested alternative combined fiber extraction procedures for the extraction of fibers from bamboo culms, with the goal of minimizing the drawbacks of separate extraction methods by using an environmentally friendly enzyme solution developed by a research group at Chengdu Textile College. The fundamental physical and mechanical properties of bamboo fibers were also investigated. The bamboo species studied were Dendrocalamus membranaceus (S-1), Neosinocalamus a±nis (S-2), Phyllostachys heterocycle (S-3), and Phyllostachys bambusoides (S-4). Bamboo fibers with 6.6-56.37 cm fiber length, 5.12-95.02 tex linear density, 100-1446 cN breaking strength, 1.2-146.5 cN/tex breaking tenacity, 0.26-3.43% breaking elongation, and 1.44-173.56 cN/tex breaking modulus values were extracted. The coarsest bamboo fibers were extracted using a combined chemical (boiling alkali)-mechanical (rolling)  echnique, whereas the bamboo fibers with the lowest average length, fineness, and breaking modulus values were extracted using a combined enzymatic-chemical (alkali)-mechanical (rolling) technique. Bamboo fibers extracted using a combined chemical (alkali at room temperature)-enzymatic (by stacking)-mechanical (rolling) technique had the lowest average breaking strength, tenacity, and elongation values but the highest average length. Bamboo fibers with the highest average breaking strength, tenacity, and modulus values were extracted using a combined chemical (alkali at room temperature)-enzymatic (in solution)-mechanical (rolling) technique. The extracted bamboo fibers exhibited variations in fundamental properties, as is typical of plant fibers. The fibers extracted using a combination of enzymatic-chemical (alkali)-mechanical (rolling) methods showed the least variation.
Keywords: Bamboo fiber extraction; Physical properties of bamboo fibers; Mechanical properties of bamboo fibers; Comparison of bamboo extraction methods